2016
DOI: 10.1111/evo.13085
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting, disrupted placental expression, and speciation

Abstract: The importance of regulatory incompatibilities to the early stages of speciation remains unclear. Hybrid mammals often show extreme parent-of-origin growth effects that are thought to be a consequence of disrupted genetic imprinting (parent-specific epigenetic gene silencing) during early development. Here we test the long-standing hypothesis that abnormal hybrid growth reflects disrupted gene expression due to loss of imprinting (LOI) in hybrid placentas, resulting in dosage imbalances between paternal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 81 publications
5
74
0
Order By: Relevance
“…There is growing evidence for a role for imprinted genes in hybrid inviability in both mammals and seed plants (e.g., Brekke & Good, ; Brekke, Henry, & Good, ; Burkart‐Waco, Ngo, Lieberman, & Comai, ; Florez‐Rueda et al., ; Garner, Kenney, Fishman, & Sweigart, ; Josefsson, Dilkes, & Comai, ; Loschiavo, Nguyen, Duselis, & Vrana, ; Vrana et al., ), and dysregulation of imprinted genes caused by trans effects has been suggested as a possible source of this incompatibility (Wolf, Oakey, & Feil, ). Intriguingly for the X‐autosome conflict hypothesis, Vrana et al.…”
Section: Other Selfish Aspects Of X Chromosomes and How They Might Comentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence for a role for imprinted genes in hybrid inviability in both mammals and seed plants (e.g., Brekke & Good, ; Brekke, Henry, & Good, ; Burkart‐Waco, Ngo, Lieberman, & Comai, ; Florez‐Rueda et al., ; Garner, Kenney, Fishman, & Sweigart, ; Josefsson, Dilkes, & Comai, ; Loschiavo, Nguyen, Duselis, & Vrana, ; Vrana et al., ), and dysregulation of imprinted genes caused by trans effects has been suggested as a possible source of this incompatibility (Wolf, Oakey, & Feil, ). Intriguingly for the X‐autosome conflict hypothesis, Vrana et al.…”
Section: Other Selfish Aspects Of X Chromosomes and How They Might Comentioning
confidence: 99%
“…There is growing evidence for a role for imprinted genes in hybrid inviability in both mammals and seed plants (e.g., Brekke & Good, 2014;Brekke, Henry, & Good, 2016;Burkart-Waco, Ngo, Lieberman, & Comai, 2015;Florez-Rueda et al, 2016;Garner, Kenney, Fishman, & Sweigart, 2016;Josefsson, Dilkes, & Comai, 2006;Loschiavo, Nguyen, Duselis, & Vrana, 2007;Vrana et al, 2000), and dysregulation of imprinted genes caused by trans effects has been suggested as a possible source of this incompatibility (Wolf, Oakey, & Feil, 2014). Intriguingly for the X-autosome conflict hypothesis, Vrana et al (2000), Zechner et al (2004) and Loschiavo et al (2007) find a large role for the X chromosome in, respectively, imprinted gene dysregulation, overgrowth phenotypes in hybrids, and abnormalities in the development of the placenta, a site of strong parentally antagonistic selection, as suggested by the abundance of imprinted gene expression there.…”
Section: Parental Antagonismmentioning
confidence: 99%
“…a model for tissue regeneration (Santos et al, 2016; Seifert et al, 2012)), deer mice ( Peromyscus sp. , models for population genetics and adaptation (Weber et al, 2013; Bedford and Hoekstra, 2015; Bendesky et al, 2017)), sandrats (a model for diet-induced diabetes (Hargreaves et al, 2017; Donath et al, 1999)), hamsters (Brekke et al, 2016; Brekke and Good, 2014) and degus ( Octodon degus (Roff et al, 2017; Correa et al, 2016, 2013)), as well as rabbits (Banszegi et al, 2009) and other mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic crosses involving multiple inbred lines are hugely powerful for genetic 71 experiments, but true inbred strains of mammals are rare outside of 'model' rodents such as mice 72 and rats. The use of 'non-model' rodents, such as gerbils (Meriones unguiculatus, (Stuermer & 73 Wetzel, 2006), hamsters (Phodopus sp., (Brekke, Henry, & Good, 2016), spiny mice (Acomys 74 sp., (Gawriluk et al, 2016) and deer mice (Peromyscus sp., (Weber, Peterson, & Hoekstra, 75 2013), is mainly restricted to outbred colonies with standing genetic variation. Unfortunately, 76 even in outbred strains of house mice genetic diversity is often ill-defined (Chia et al, 2005), and 77 surprisingly little work has been done to quantify diversity in colonies of non-model rodents.…”
Section: Introduction 47mentioning
confidence: 99%